KONSTRUKSI MAKNA CANTIK BAGI MAHASISWI UNIVERSITASRIAU BERKULIT COKELAT - Retno Sari; Noor Efni Salam (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Beauty with white-skinned being ideal for women, due to the fact that the of beauty has been constructed by some idelogies that linked to the flow of information giuen by the media making the most of societies or sororities disired to look beauty and attractived with the white-skinned. While the community of Indonesian mentionedl their skin as brown or yellow ripe as type V. Nevertheless, among women who are proud of their beautiful brown-skined because the meaning of beauty for each individual varies based on the knowledge and understanding in constructing the meaning of beauty. This research aims to know the meaning of beauty and experience of communication for brown-skinned coed Riau University. This research used qualitative research methods with the phenomenology approach. The research subject consists of five brown-skinned coeds University of Riau, who selected by using two categories 3 people used incidental sampling technique and 2 people the used snowball. The technique of data collection was conducted through interview, observation, as well as documentation. The results of this research showed that are as follows the firstly, the meaning of beauty for brown-skinned Coed University of Riau which consist of the outside beauty that is fair skinned, good-looking, clean, and face. While the beauty from inside the soul, the heart, intelligence, mind and personality. Secondly, the experience of communication are categorized into two categories, the sweet communication experience be a good acceptance, support from family, neighbors, friends, girlfriends and humour that make family relationships become close and harmonious, get more attention, get a beloued call, get a lovely compliment, unique characters and not boring. And bitter communication experience such as rejection from family, neighbors, friends, opposite sex, the subject of humour, get mock, insults or pressure, get a new nicknam, less confident with the opposite sex, and hard to match the right clothes with skin color.Keyword: meaning beauty, Coed, Brown-skinned